2021
DOI: 10.1111/fme.12504
|View full text |Cite
|
Sign up to set email alerts
|

Hatch timing of two subarctic salmonids in a stream network estimated by otolith increments

Abstract: Early life history ecology, in particular timing of hatch, is important in understanding population dynamics and community structure of stream salmonids. Larval stages are vulnerable to predation and physical disturbances, and their production is often regulated by annual variation in timing and magnitude of high flow events during egg incubation and post-hatch periods (Kovach et al., 2016). Timing of hatch influences variation in body size in early life stages (Yamamoto et al., 1997), which then mediates intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Specifically, the magnitude of maximum spring flow was considerably higher in the northern sub‐region, which would more likely result in stream bed scouring and YOY mortality in the northern versus southern sub‐region. Plus, winter stream temperature during trout egg incubation was warmer in the southern sub‐region relative to the northern sub‐region (G. Valentine, unpublished data), which accelerates egg development in salmonids and generates latitudinal variation in hatch timing (Fitzgerald et al., 2021; Yamamoto et al., 1997). Consequently, body size of YOY in the northern populations may be smaller and more often subject to mortality‐causing high flow events in spring than those in the southern populations, a hypothesis that needs to be tested with broad‐scale studies of early life histories.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the magnitude of maximum spring flow was considerably higher in the northern sub‐region, which would more likely result in stream bed scouring and YOY mortality in the northern versus southern sub‐region. Plus, winter stream temperature during trout egg incubation was warmer in the southern sub‐region relative to the northern sub‐region (G. Valentine, unpublished data), which accelerates egg development in salmonids and generates latitudinal variation in hatch timing (Fitzgerald et al., 2021; Yamamoto et al., 1997). Consequently, body size of YOY in the northern populations may be smaller and more often subject to mortality‐causing high flow events in spring than those in the southern populations, a hypothesis that needs to be tested with broad‐scale studies of early life histories.…”
Section: Discussionmentioning
confidence: 99%
“…After the establishment of the emergence check, growth often accelerates and therefore subsequent rings are further apart and more translucent (Campana, 2001; Campana & Neilson, 1985). Other work has shown that hatch and emergence times can be inferred in wild salmonids based on otolith microstructure (Fitzgerald et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Other work has shown that hatch and emergence times can be inferred in wild salmonids based on otolith microstructure (Fitzgerald et al 2021).…”
Section: Otolith Work and Hatch Datementioning
confidence: 99%
“…After the establishment of the emergence check, growth often accelerates and therefore subsequent rings are further apart and more translucent (Campana, 2001 ; Campana & Neilson, 1985 ). Other work has shown that hatch and emergence times can be inferred in wild salmonids based on otolith microstructure (Fitzgerald et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%